2022
DOI: 10.1107/s2059798322000948
|View full text |Cite
|
Sign up to set email alerts
|

A new inactive conformation of SARS-CoV-2 main protease

Abstract: The SARS-CoV-2 main protease (Mpro) has a pivotal role in mediating viral genome replication and transcription of the coronavirus, making it a promising target for drugs against the COVID-19 pandemic. Here, a crystal structure is presented in which Mpro adopts an inactive state that has never been observed before, called new-inactive. It is shown that the oxyanion loop, which is involved in substrate recognition and enzymatic activity, adopts a new catalytically incompetent conformation and that many of the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 79 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…In summary, for 5R83-Luteolin-7-O-glucoside, 5R83-Demethyloleoeuropein, and 5R83-Oleuropein aglycone, many hydrogen bonds were established between Thr24, Thr26, Asn142, Gly143, Ser144, Glu189, and the binding pocket- 2 of M pro were observed, indicating that these amino acid residues interact strongly with the ligands in all possible directions. Similarly, with several studies, we found His41 and Cys145 (catalytic dyad) strongly interact with both Demethyloleoeuropein and Oleuropein aglycon [37] , [38] , [39] , [40] . Additionally, for 5R83-Luteolin-7-O-glucoside 5R83-Demethyloleoeuropein and 5R83-Oleuropein aglycone water bridges were existed in parallel along with hydrogen bonding in the majority of residues ( Figure 8 ).…”
Section: Resultssupporting
confidence: 87%
“…In summary, for 5R83-Luteolin-7-O-glucoside, 5R83-Demethyloleoeuropein, and 5R83-Oleuropein aglycone, many hydrogen bonds were established between Thr24, Thr26, Asn142, Gly143, Ser144, Glu189, and the binding pocket- 2 of M pro were observed, indicating that these amino acid residues interact strongly with the ligands in all possible directions. Similarly, with several studies, we found His41 and Cys145 (catalytic dyad) strongly interact with both Demethyloleoeuropein and Oleuropein aglycon [37] , [38] , [39] , [40] . Additionally, for 5R83-Luteolin-7-O-glucoside 5R83-Demethyloleoeuropein and 5R83-Oleuropein aglycone water bridges were existed in parallel along with hydrogen bonding in the majority of residues ( Figure 8 ).…”
Section: Resultssupporting
confidence: 87%
“…Its catalytic activity revolves around the processing of two overlapping polyproteins, namely pp1a and pp1ab, which leads to the formation of 16 mature non-structural proteins (NSPs) 75 . Composed of 306 amino acids, the SARS-CoV-2 M pro shares 96% sequence identity and a highly conserved three-dimensional structure with the SARS-CoV M pro (0.53 Å R.M.SD between PDB entries 6Y2E and 2BX4) 76 , 77 . Although a dynamic equilibrium between a monomeric and a dimeric form exists, only the dimer is responsible for the protease’s enzymatic activity 78 , 79 .…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic site is a shallow, solvent-exposed cavity that is formed by several sub-pockets that are responsible for the recognition of various residues composing the substrate peptide sequences 76 , 80 . Concerning this, particularly important is the conserved sequence Gln↓-Ser, where Gln↓- indicates the glutamine residue that precedes the cleavage site 81 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have contributed to thoroughly characterising the nature of the shallow and solvent-exposed catalytic site of the SARS-CoV-2 28 , which has proven to be readily investigable with both time-dependent and time-independent structure based-approaches such as molecular docking 29 and molecular dynamics 30 , leading to the development of compounds with affinities in the low nanomolar range 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%